Coal combustion and lung cancer risk in XuanWei: a possible role of silica? / Combustione di carbone e rischio di tumore polmonare in XuanWei: un possibile ruolo della silice? - Vermeulen, R.; Rothman, N.; Lan, Q. (La Medicina del Lavoro, 2011)
SummaryBackground: XuanWei County, Yunnan province, has the highest lung cancer mortality rates among men and women in China. The high mortality has been linked to the use of smoky (bituminous) coal for heating and cooking. Research to date has suggested that exposure to polycyclic aromatic hydrocarbons (PAHs) is one of the main contributors to the observed risk. More recently exposure to crystalline silica has been suggested as another contributing factor. Methods: We used data of indoor benzo[a]pyrene (BaP) and silica level and lung cancer mortality at the communal level from previous reports to discuss etiological hypotheses on the lung cancer epidemics in XuanWei County. Results: We estimated that PAH exposure as measured by benzo[a]pyrene (BaP) can explain a significant part of the excess risk but not fully (Odd Ratio (OR) ~ 3 as compared to an observed OR=8 for smoky coal users versus smokeless coal users). This leaves open the possibility of other contributing exposures. Exposure to crystalline silica however would likely only result in an increased risk (OR) of less than 1.5 and as such silica seems not to be the main exposure of interest. However, this does not exclude that risks are present because of the specific physic-chemical characteristics of the silica in smoky coal or that there is an interaction between silica and PAH exposures. Conclusion: More detailed exposure assessment of indoor air pollution due to the use of smoky coal and subsequent linkage on an individual level to ongoing epidemiological studies should provide more insight in the etiology of lung cancer in this region.